Paul Robeson and the End of His “Movie” Career - Musser, Charles (Cinémas, 2008)
AbstractPaul Robeson made his last fiction film appearance in Tales of Manhattan (directed by Julien Duvivier, 1942), which the black star ended up denouncing for its demeaning racial stereotypes. Robeson scholars have echoed this negative assessment while French critics have likewise dismissed the film as a minor effort in Duvivier’s oeuvre. This article reassesses and resituates the film historically, arguing that the black-cast sequence, when viewed intertextually, was much richer and more progressive than generally appreciated. In production before World War II and released almost ten months after Pearl Harbor, Tales of Manhattan was historically out of sync.